Evaluation of progression of chronic kidney disease in dogs with myxomatous mitral valve disease - Yun, Hyejin; Koo, Yoonhoi; Yun, Taesik; Chae, Yeon; Lee, Dohee; Cha, Sijin; Kim, Jeeyune; Kim, Hakhyun; Yang, Mhan Pyo; Kang, Byeong Teck (Frontiers in Veterinary Science, 2023)
Introduction: Cardiovascular and renal diseases are known to affect each other in the cardiovascular renal axis disorder (CvRD). Although CvRD, which includes myxomatous mitral valve disease (MMVD) and chronic kidney disease (CKD), has been described in dogs, there are only a few reports on the progression of CKD in accordance with the severity of MMVD. The aim of this study was to evaluate whether the presence of MMVD is associated with the rate of progression of CKD in dogs. The time from the initial diagnosis to the worsening of the International Renal Interest Society (IRIS) stage and the time for the occurrence of hyperphosphatemia and isosthenuria were evaluated.In this retrospective study, CKD progression was determined as an increase in the IRIS stage by at least one level and the development of hyperphosphatemia or isosthenuria. The CKD progression was compared in dogs with and without comorbid MMVD.Results: Dogs with CKD were divided into two groups: dogs with and without MMVD (n = 63, concurrent group; n = 52, CKD group, respectively). The concurrent group was further divided into two subgroups based on the American College of Veterinary Internal Medicine guidelines (B1 group, n = 24; B2 group, n = 39). The time for progression of CKD from IRIS stage 1 to IRIS stage 2 was significantly shorter in the concurrent group than in the CKD group (log-rank test, P < 0.001). MMVD was associated with an increased risk of progression from stage 1 to stage 2 (hazard ratio, 6.442; 95% confidence interval (CI), 2.354 to 18.850; P < 0.001). The timing of the onset of hyperphosphatemia or isosthenuria in the concurrent group and the CKD group was not significantly different.